Rehabilitation of a patient with palatal defect- A case report - Sadeq Mohammed Taqi Fadhil; Emre Mumcu (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Defects in the jaw and face area are caused by congenital anomalies and some infections. In this study, we present a case of palatal insuffi ciency after maxillectomy, treated with shutter which was applied to ensure the aesthetics, phonation and functional defi ciency of the patient.